Can a periodically driven particle resist laser cooling and noise? - A. Maitra; D. Leibfried; D. Ullmo; H. Landa (Physical Review Research, 2019)
Studying a single atomic ion confined in a time-dependent periodic anharmonic potential, we find large amplitude trajectories stable for millions of oscillation periods in the presence of stochastic laser cooling. Accounting for the complexity of the laser cooling process we calculate the details of the effective dynamics away from thermal equilibrium. The competition between energy gain from the time-dependent drive and damping leads to the stabilization of such stochastic limit cycles. Instead of converging to the global minimum of the averaged potential, the steady-state phase-space distribution develops multiple peaks in the regions of phase space where the frequency of the motion is close to a multiple of the periodic drive. Such distinct nonequilibrium behavior can be observed in realistic radio-frequency traps with laser-cooled ions, suggesting that Paul traps offer a well-controlled test bed for studying the transport and dynamics of microscopically driven systems.